On the History of Old Believer in Lithuania in 19th Century: Rimkai Old Believer Church Assembly in 1856 and its Resolutions - Nadežda Morozova (Vilnius University Press, 2021)
The history of Old Believers in Lithuania in the 19th century is insufficiently studied. Well, we know the main centers, events and names of the most important figures, the key moments in the history of the Old Believer society are identified. But there are any generalizing monographs in this field and now the main task is to accumulate empirical material and try to put them in a future common historical narrative.